Gênero discursivo propaganda impressa: uma experiência pedagógica - Nunes, Eunice Ferreira (2010)
This dissertation aims as object research the study of discursive gender, print advertising, found in textbooks and assessments of public state, as SARESP and ENEM. Had as a starting point to analyze print advertising and describe the main characteristics of the gender, emphasizing the link between the verbal and visual language, always in articulated way the conditions of production, circulation and reception of texts. To direct the way of this research, was performed an analysis based on current proposals for education that has the in the discursive gender, the Bakhtinian sense of the term, the basic units of education. The corpus chosen for this research consisted of ten proposals for reading of discursive gender print advertising at the school. The research shows that, to obtain an actual reading of the dircursive gender in our life, is necessary that students know and identify the most resources verbal and nonverbal present in this gender. This research may provide grants to teachers, to them can plan work activities using the discursive gender, in the classroom, in a way more complete and enriching